DIREITOS HUMANOS E MEIO AMBIENTE: A EDUCAÇÃO AMBIENTAL COMO FORMA DE FORTALECER A INTERRELAÇÃO - Hammarston, Fátima Barasuol; Cenci, Daniel Rubens (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704244 Our times, human rights cannot continue to be seen and analyzed in isolation andrelative, it is necessary to consider the universalization of them within the context of historical,cultural and economic development that is taking place in modern society. Such a society hasturned to consumerism and the fluidity of relationships. The purpose of an interdisciplinary andcritical human rights, it is indisputable and necessary. Linking Human Rights and the Right to anecologically balanced environment, leads to thinking about sustainability and ensuring sustainabledevelopment presents itself as one of the concerns of researchers, governments, regulators, including internationally. It is not enough awareness of issues involving human rights and theenvironment as part of this, but we need to rethink (re) act mean, more precisely, of variousshapes, individually and collectively, through measures of personal character, which run throughthe execution of an environmental education focused on the reformulation of environmental andsustainability concepts. In this sense, the right to an ecologically balanced environment emergesas a fundamental right of every human being, and therefore a right which must have its basis in anenvironmental consciousness that permeates an environmental education toward aninterrelationship between the environment and rights human.